2005
DOI: 10.1002/jsfa.2113
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds in some apple (Malus domestica Borkh) cultivars of organic and integrated production

Abstract: Eleven organically grown apple cultivars and 11 apple cultivars of integrated production from Austria and Slovenia were analyzed by HPLC for the content of phenolic compounds in peel and pulp. We identified chlorogenic acid, p-coumaric acid, procyanidin B3, protocatechuic acid, (−)-epicatechin, phloridzin, rutin and quercetin-3-rhamnoside in apple peel. In apple pulp, (+)-catechin was also identified in all the cultivars. Some other phenols (procyanidin B3, rutin and quercetin-3-rhamnoside) could not be identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
120
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 174 publications
(145 citation statements)
references
References 13 publications
(15 reference statements)
19
120
1
4
Order By: Relevance
“…By focusing on the phenols in two types of Annurca apple, we found that the organically grown variety contained many more phenols in contrast to those grown in a conventional way. A different content in polyphenols was also reported by Veberic et al [17] and Hecke et al [18], which studied several organic and integrated varieties of apple. Generally, the content of polyphenols may be expected in vegetable organisms also as reaction against biotic or abiotic stress.…”
Section: Total Phenol Contentsupporting
confidence: 65%
“…By focusing on the phenols in two types of Annurca apple, we found that the organically grown variety contained many more phenols in contrast to those grown in a conventional way. A different content in polyphenols was also reported by Veberic et al [17] and Hecke et al [18], which studied several organic and integrated varieties of apple. Generally, the content of polyphenols may be expected in vegetable organisms also as reaction against biotic or abiotic stress.…”
Section: Total Phenol Contentsupporting
confidence: 65%
“…previously obtained by other authors [7,14,19]. In the pulp of organically produced apples, a significantly higher total phenolic content was measured compared with the pulp of apple from the other three treatments, respectively.…”
Section: Table IVsupporting
confidence: 58%
“…According to many authors [14,27,28], higher phenol concentration in organically grown fruits can be attributed to severe forms of biotic or abiotic stress, which is known to induce phenolic biosynthesis. However, this theory cannot be applied universally, since there are examples in the literature where the content of phenolic compounds did not significantly differ between organically and conventionally produced fruit [7] or was even lower in organically produced fruit [29].…”
Section: Table IVmentioning
confidence: 99%
See 2 more Smart Citations